Model of developing artistic and creative cultural values in prospective vocational education teachers - Umralieva, Laura; Tanirbergenov, Medeubek; Mussakulov, Kussan; Beisenbekov, Zhalgasbek; Kerimbai, Balkiya (Frontiers in Education, 2025)
In the current era of globalization, there is an increasing need to cultivate individuals who are not only intellectually enriched through the advancement of education, science, art, and culture but also creatively developed and culturally competent. Such individuals must be capable of integrating artistic creativity into their professional activities. In this context, fostering artistic and creative cultural values among prospective vocational education teachers emerges as a new and important area of research. This study aims to develop a structural-content model for developing artistic and creative cultural values in prospective vocational education teachers. The proposed model comprises three key components: target, content-procedural, and diagnostic-outcome sections. As part of the model, an elective course titled “artistic and creative cultural values” was developed. This course is designed to equip students with professional knowledge and creative skills necessary for organizing art-based instruction and engaging them in the appreciation and cultivation of artistic and creative cultural values.